Designing and analyzing an event service for sensor networks - Gujrati, Sumeet (Kansas State University, 2008)
This work is motivated by the OMG’s CORBA Event Service Specification. CORBA is the acronym for Common Object Request Broker Architecture. In this research, we implemented and analyzed an event service using a model similar to the OMG model for sensor networks applications which are written in nesC programming language, an extension of C programming language. This implementation has been tested on a test bed created using Crossbow’s TelosB motes and Crossbow’s Stargate Netbridge modules as gateways. Event service interface implementations, which reside on the motes, are written in nesC. The data routing part, which is done through Stargate Netbridges, is written in the C language. This document contains experimental results obtained by deploying and running the implementation on the test bed.
Keywords: Event Service; Sensor Network; Computer Science (0984)